Fundamentals of Entrepreneurship (ENT300) : Chacha Cake House / Mohamad Nadeem Arbi … [et al.] - Arbi, Mohamad Nadeem; Arifin, Rafiq Syahmi; Rakawi, Danial Fitri; Abang Mohamad, Abang Hamizan (2018)
ChaCha Cake house is a business that focusing on the bakery which to serve and satisfy the customer taste and expectation. Our mission for our bakery is to becoming the successful which is the best among another bakery and be a well known bakery whether internationally and domestically by producing and assure that our quality for the product is good and meet what the customer expected. Our business "ChaCha" is a private limited company business that involved 4 people to run our business. Before establish our business, each of the partner need to contributed RM21304 as stated in the agreement. ChaCha Cake house is a bakery that produce and sell bread, croissant,tart and cakes which every student and working people will mostly need to find the simple and affordable food to fill their own stomach